ANALISIS YURIDIS NORMATIF: KEWENANGAN PENERBITAN RESEP KACAMATA DAN IMPLIKASINYA TERHADAP KLAIM ASURANSI KESEHATAN DI INDONESIA - Riono, YV Agung; Ginting , James Davidta; Simarmata, Murni; Efendi , Zakaria (Akademi Refraksi Optisi dan Optometry Gapopin, 2026)
Regulatory Reform in Health through Law No. 17 of 2023 on Health has introduced a paradigmatic shift in the governance of health professionals in Indonesia. One of the fundamental changes worth noting is the clear demarcation between medical practitioners (physicians and dentists) and other health professionals, alongside the strengthening of optometrists’ professional authority within the domain of medical technical expertise. This study aims to analyze the scope of optometrists’ authority in issuing eyeglass prescriptions following the enactment of the 2023 Health Law and to examine its compatibility with health insurance claim requirements, particularly under BPJS Kesehatan. Employing a normative juridical research method with statutory and conceptual approaches, this study finds a dissonance between the health law regime, which grants professional autonomy to optometrists, and the social security law regime, which continues to require prescriptions from ophthalmologists. The study recommends regulatory harmonization across sectors and the reinforcement of the role of the Indonesian Health Professionals Council in ensuring the quality of optometric services.